2013
DOI: 10.1016/j.jaip.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Peer Support and mp3 Messaging on Adherence to Inhaled Corticosteroids in Minority Adolescents with Asthma: A Randomized, Controlled Trial

Abstract: Background Poor adherence to inhaled corticosteroids (ICS) is a critical risk factor contributing to asthma morbidity among low-income minority adolescents. Objective This trial tested whether peer support group meetings and peer asthma messages delivered via mp3 players improved adherence to ICS. Methods Low-income African American and/or Hispanic adolescents, ages 11–16, with persistent asthma, and poor (≤ 48%) adherence to prescription ICS during the 3-week run-in were randomized to intervention or atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 39 publications
1
62
0
2
Order By: Relevance
“…Pediatric studies using both self-report and objective measures to capture adherence to ICS demonstrate significant overestimation of adherence by the former approach. 10,36,37 It is crucial to have accurate adherence data in order to draw reliable conclusions between levels of adherence and potentially associated factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric studies using both self-report and objective measures to capture adherence to ICS demonstrate significant overestimation of adherence by the former approach. 10,36,37 It is crucial to have accurate adherence data in order to draw reliable conclusions between levels of adherence and potentially associated factors.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the trial have been published previously. 10 Prior to randomization, participants completed a 3-week run-in period to assess baseline characteristics and determine eligibility for participation in a 10-week active treatment phase. Adherence to ICS was measured over the last 14 days of the 21 day run-in period using an objective electronic adherence monitor.…”
Section: Methodsmentioning
confidence: 99%
“…There are few studies focusing on the influences of peers on medication adherence of youth diagnosed with asthma. The use of peer asthma educators is associated with increases in adherence; however, using a peer support group is not effective in improving adherence compared to control . Heightened asthma stigma (eg, feeling embarrassed to take asthma medications at school) is linked to decreased adherence …”
Section: Resultsmentioning
confidence: 99%
“…A careful review of the literature reveals that among minority populations with asthma, only 11 randomized controlled trials using different forms of electronic media have been reported. [25][26][27][28][29][30][31][32][33][34][35] All but one of the previously reported studies was conducted in children or adolescents, and the study performed in adults was not successful. 32 The duration of these studies ranged from 1 month to 1 year, and nearly all required special staffing (ie, nurses, asthma counselors, or asthma coaches) for completion.…”
Section: Discussionmentioning
confidence: 99%